2018
DOI: 10.2169/internalmedicine.9831-17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Impairment of the Vascular Endothelial Function and the CHA<sub>2</sub>DS<sub>2</sub>-VASc Score in Patients with Sinus Rhythm and Non-valvular Atrial Fibrillation

Abstract: Objective and methods There is little information concerning the influence of the heart rhythm on the vascular endothelial function in patients with non-valvular atrial fibrillation (AF) compared with studies concerning sinus rhythm (SR). The present study included paroxysmal (n=184) or chronic (n=53) AF patients without heart failure and control subjects with SR (n=79) matched for age, gender and the CHA2DS2-VASc score. Paroxysmal AF was defined as episodes that terminated spontaneously within 7 days, while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…The results are consistent with other studies looking at FMD in hypertension and AF individually and confirms that endothelial dysfunction is present. 9,[13][14][15][16]21 Our findings extend previous work by demonstrating that the presence of AF generally does not incrementally worsen endothelial dysfunction, nor was AF an independent predictor of endothelial dysfunction on multivariate analysis. However, permanent AF compared to paroxysmal AF does have significantly worse FMD parameters with permanent AF being an independent predictor on multivariate analysis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results are consistent with other studies looking at FMD in hypertension and AF individually and confirms that endothelial dysfunction is present. 9,[13][14][15][16]21 Our findings extend previous work by demonstrating that the presence of AF generally does not incrementally worsen endothelial dysfunction, nor was AF an independent predictor of endothelial dysfunction on multivariate analysis. However, permanent AF compared to paroxysmal AF does have significantly worse FMD parameters with permanent AF being an independent predictor on multivariate analysis.…”
Section: Discussionsupporting
confidence: 78%
“…[9][10][11][12] FMD is also found to be impaired in patients with AF. [13][14][15][16] Since AF and hypertension, commonly co-exist, we hypothesised that endothelium-dependent FMD will be reduced in patients with AF (and hypertension) compared to hypertensive controls and this may partly explain the poor prognosis in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support the notion that AF patients demonstrate an impaired FMD 7,8 . Indeed, Komatsu et al found that FMD also related to AF severity, with an FMD of 6.5 ± 3.5% in non‐AF individuals, 5.4 ± 2.6% in paroxysmal AF patients, and 4.3 ± 2.1% in chronic AF patients 9 . A 1% drop in FMD relates to a 13% increase in cardiovascular risk 10 .…”
Section: Endothelial Dysfunction and Vascular Maladaptation In Primary Prevention Of Afmentioning
confidence: 85%
“…7,8 Indeed, Komatsu et al found that FMD also related to AF severity, with an FMD of 6.5 ± 3.5% in non-AF individuals, 5.4 ± 2.6% in paroxysmal AF patients, and 4.3 ± 2.1% in chronic AF patients. 9 A 1% drop in FMD relates to a 13% increase in cardiovascular risk. 10 The impaired FMD in AF patients may be restored following cardioversion, 8 with preserved FMD after catheter ablation if sinus rhythm is maintained.…”
Section: Endothelial Dysfunction and Vascular Maladaptation In Primmentioning
confidence: 99%
“…Atrial fibrillation (AF) is an important heart rhythm disorder common in clinical practice, which causes hemodynamic disorders, frequent hospitalizations, and thromboembolic events, and affects 1-2% of the general population (3). Although the exact mechanisms causing AF are not fully understood, hypertension, heart failure, diastolic dysfunction, endothelial dysfunction and left ventricular hypertrophy play an important role in the pathogenesis of AF (3,4 ). Side effects such as hypertension, diastolic dysfunction, endothelial dysfunction, left ventricular hypertrophy can also be seen in PHPT disease (2) .…”
Section: Introductionmentioning
confidence: 99%